EFEKTIVITAS IMPLEMENTASI PROGRAM FIRST IN FIRST OUT (FIFO) PADA PEMBUATAN SIM DALAM MENUNJANG SMART SERVICE POLRESTA BANDAR LAMPUNG - Mita Sari; Agustuti Handayani; Muhammad Ardiansyah (Jurnal Progress Administrasi Publik (JPAP), 2022)
This study analyzes the implementation of the First In First Out (FIFO) program in SIM making in supporting the Smart Service Polresta Bandar Lampung. The study was conducted to determine and analyze the effectiveness of the program, the inhibiting and supporting aspects of the First In First Out (FIFO) program in SIM making in supporting the Smart Service Polresta Bandar Lampung. In analyzing the Effectiveness of Program Implementation, the author uses Richard's (2009) Effectiveness theory with the variables of Achieving Goals, Integration and Adaptation and supported by Edward III's Theory (Purwanto: 2015) with variables, Resources, Communication, Disposition and Bureaucratic Structure which are used as tools to measure program effectiveness. , so that it will be seen whether the government's efforts in implementing a series of Program Implementation have been effective or not. This research uses a qualitative research type, with a qualitative descriptive approach/case study. Case studies are research on humans (in the form of groups, organizations, or individuals) and events/phenomena that occur in the community. Data collection was obtained from the interview process with several informants, observations and documentation. The results of the research are the implementation of the First In First Out (FIFO) program on SIM making which has not been effective in an effort to improve the Smart Service of the Bandar Lampung Police. This is indicated by the lack of coordination between stakeholders, the aspect of resources that have not been effective in terms of quality and quantity and the communication and socialization strategies that have been carried out have not been maximized. Â  Keywords: Effectiveness, Program implementation, First In First Out (FIFO), Bandar Lampung Police.